Quality assessment on the long-term cryopreservation and nucleic acids extraction processes implemented in the andalusian public biobank - Ortega-Pinazo, J.; Díaz, T.; Martínez, B.; Jiménez, A.; Pinto-Medel, M. J.; Ferro, P. (Cell and tissue banking, 2019)
Human samples are commonly collected and long-term stored in biobanks for current and future analyses. Even though techniques for freezing human blood are well established, the storage time can compromise the cell viability as well as the yield and quality of nucleic acids (RNA and DNA) extracted from them. In this study, a protocol to obtain peripheral blood mononuclear cells (PBMCs) from 70 subjects, which were stored at − 196 °C from EDTA tubes for a long-term, was assessed. In parallel; a protocol to obtain DNA from the same subjects, which were stored at − 80 °C from citrate tubes, was also studied. Samples stored from 2008 to 2012 were studied and the results obtained showed that there were no statistically significant differences in the RNA or DNA extracted in terms of purity, integrity and functionality The freezing protocol used by the Málaga Biobank shows that viable PBMCs and DNA could be kept for a period of, at least, 10 years, with a high quality and performance. Furthermore, RNA extracted from these PBMCs presents also a good quality and performance. Therefore, the samples frozen according to the conditions of the protocols assessed in this study could be optimal for biomedical research.